Statistical analysis of the differences of head and face features between terracotta warriors and modern multi ethnic groups based on 3D information extraction. Issue 1 (May 2021) - Hu, Yungang; Wang, Jingyang; Lan, Dexing
Abstract: The terracotta warriors excavated from Qin Shihuang's mausoleum are precious materials of the Qin Dynasty. They have great historical, scientific and artistic research value and are considered to be the true portrayal of the Qin people. In anthropology, the measurement of head and face features is one of the important means to analyze the ethnic relationship. In this paper, the 3D laser scanner is used to collect the high-precision 3D point cloud data of the terracotta warriors, extract the head and face features of the terracotta warriors, and variance analyze (ANOVA) and cluster analysis with the collected head and face features of 29 modern ethnic groups. Variance analysis shows that there is no significant difference between the terracotta warriors and modern people in the shape of morphological facial length, bizygomatic breadth, nose height, the height of mucons lips, and mouth breadth. Cluster analysis based on head and face features shows that the terracotta warriors belong to the same group with 10 ethnic groups including Mongolian, and they have more similar head and face features.